Development of animation-based learning media with music and song lyrics on the cell division material at Al-Bahra High School Jeneponto Regency - Wahyuddin Wahyuddin; Jamilah Jamilah; Eka Damayanti; Andi Maulana (Universitas PGRI Semarang, 2022)
Learning media in the teaching and learning process has many uses or functions that significantly strengthen the learning objectives. This research aimed to develop learning media based on animation and song lyrics on cell division material for senior high school students and determine its validity, practicality, and effectiveness. This study used the Research and Development method referred to ADDIE model. The model consisted of five stages (analysis, design, development, implementation, and evaluation). The product developed was animation-based learning media with music and song lyrics and was tested through validity tests, practice tests, and effectiveness tests. The research instruments were validation sheets to validate the media by experts, a response questionnaire to collect information from educators and students regarding the practicality of the media, and learning outcomes tests given to students. In this study, the product was tested on class XII senior high school students of Al-Bahra, Jeneponto, Indonesia. The results showed the validity level of the media was 3.68 with the very valid category. The practicality level of the media was 3.56 with the very practical category with the percentage of the effectiveness rate was 85.71% with the effective category. This study concludes that animation-based learning media with music and song lyrics on cell division material is available in the learning process because it has met the valid, practical, and effective criteria.